Screen detection is a survival predictor independent of pathological grade in colorectal cancer. A prospective cohort study. Issue 1 (February 2021) - Chan, Yen Ming; MacKay, Craig; Ritchie, Duncan T; Scott, Neil; Parnaby, Craig; Murray, Graeme I.; Ramsay, George
Abstract: Introduction: Patients with screened detected colorectal cancer (CRC) have a better survival than patients referred with symptoms. This may be because of cancers being identified in a younger population and at an earlier stage. In this study, we assess whether screened detected CRC has an improved outcome after controlling for key pathological and patient factors known to influence prognosis. Method: This is a cohort study of all CRC patients diagnosed in NHS Grampian. Patients aged 51–75 years old between June 2007 and July 2017 were included. Data were obtained from a prospectively maintained regional pathology database and outcomes from ISD records. All-cause mortality rates at 1 and 5 years were examined. A Cox proportional hazards regression model was used to estimate the effect of screening status, age, gender, Duke stage, tumour location, extramural venous invasion (EMVI) status and lymph node ratio (LNR) on overall survival. Results: Of 1618 CRC cases, 449 (27.8%) were screened and 1169 (72.2%) were symptomatic. Screened CRC patients had improved survival compared to non-screened CRC at 1 year (88.9% vs 83.9% p < 0.001) and 5-years (42.5% vs 36.2%; p < 0.001). On multivariable analysis of patients who had no neoadjuvant therapy (n = 1272), screening had better survival (HR 0.57; 95% CI 0.44–0.74; p < 0.001). EMVI (HR 2.22; CI 1.76 to 2.79; p < 0.001) and tumour location were found to affect outcome. Conclusion: Patients referred through screening had improved survival compared with symptomatic patients. Further research could be targeted to determine if screened CRC cases are pathologically different to symptomatic cancers or if the screening cohort is inherently more healthy.